Clinical and economic burden of immune tolerance induction in entire patients with hemophilia A: Insights from a real-world Korean setting - Kim, Ah Young; Baek, Hee Jo; Lee, Sukhyang; Choo, Eunjung; Park, Young Shil; Lee, Hankil (Thrombosis Research, 2024)
Introduction: The most notable challenge facing hemophilia A treatment is the development of inhibitors against factor VIII, resulting in increased clinical and socioeconomic burdens due to the need for expensive bypassing agents (BPAs). Although immune tolerance induction (ITI) is currently the primary approach for inhibiting and reducing the inhibitors, the lengthy duration of ITI necessitates the continued use of BPA to manage bleeding episodes. In this study, we aimed to obtain real-world evidence on the clinical and economic aspects and associated burdens experienced by patients with hemophilia A with inhibitors undergoing ITI in Korea. Methods: Claims data from January 1, 2007, to December 31, 2020, were used in this study. The study cohort comprised patients with hemophilia A undergoing ITI, who were categorized into three groups: successful, failed, or continuation of ITI. We evaluated clinical and economic burdens, including monthly healthcare visits, medication costs, and total medical expenses. Results: The study involved 33 cases of ITI across 32 patients. Excluding seven continuation cases where success could not be determined at the observation point, the estimated success rate of ITI was 80.8 %. The median duration of ITI for all patients was 25.7 months. While no significant disparities were noted in the ITI duration between successful and unsuccessful cases (24.51 vs. 25.66 months), substantial discrepancies were observed in the duration of BPA usage (11.10 vs. 25.66 months) and the number of prescribed BPAs (1.79 vs. 2.97). Conclusion: Successful ITI reduced both clinical and economic burdens, resulting in decreased monthly medication expenses and overall medical costs.
Keywords: Adolescent; Adult; Child; Child, Preschool; Cost of Illness; Factor VIII; Female; Health Care Costs; Hemophilia A; Humans; Immune Tolerance; Infant; Male; Republic of Korea; Young Adult; Blood coagulation factors; Cost of illness; Health expenditures; Hemophilia A; Immune tolerance